Measurement of CO, CO2, Particulate Matter (PM10), Cockpit and Ambient Temperature, Humidity and Noise Level at UTHM Hangar - Kandasamy, Bhuvarhyshie; Nor Salim, Nor Adrian; Mohd Afandi, Mohd Azizi; Bin Ali, Yaacub Zaki; Azmir, Nor Azali; Kasron, Md Zainorin (Progress in Aerospace and Aviation Technology, 2022)
This study is focussed on works that are done at the hangar and its effect on human health. The absence of proper air quality or noise level study at the current UTHM hangar has inspired to conduct this study. The objective of this study is to measure the emission rate of carbon monoxide (CO), carbon dioxide (CO2), particulate matter (PM10), and measure the cockpit temperature, ambient temperature, humidity, and noise level of PT6A-20 engine to obtain the data at the Universiti Tun Hussein Onn Malaysia (UTHM) Hangar. There are presence of 2 engines which are Lycoming O-360 and turboprop PT6A-20 at the hangar. Lycoming O-360 uses avgas and turboprop PT6A-20 uses jetA1 fuel type which will produce higher rate of emission and that is the reason of PT6A-20 engine being chosen. So this study aims to highlight a comprehensive data of CO, CO2, particulate matter (PM10), cockpit and ambient temperature, humidity and noise level regarding the turboprop PT6A-20 engine at hangar of UTHM to aid future researchers and ensure the air quality and safety rules of the hangar. The air quality standards are used as guideline are the Malaysia Ambient Air Quality Standard and Indoor Air Quality Standard based on the Department of Occupational Safety and Health (DOSH). Also, Occupational Safety and Health (Noise Exposure) Regulations 2019 is used as the standard for noise level. Q-Trak Plus IAQ Monitor model 8554 is used to measure the emission rate of CO,CO2, level of humidity and cockpit temperature. Dust Trak Aerosol Monitor is used to measure the emission rate of PM10, Pico Data Logger is used to measure the ambient temperature and finally 1352H integrating sound level meter was used to measure the noise level of PT6A-20 engine. Based on the results produced, only carbon monoxide and carbon dioxide are below than the safety limit. The othe 5 parameters which are PM10, cockpit and ambient temperature, humidity and noise level are above the allowable limit according to DOSH.